Perorally active nanomicellar formulation of quercetin in the treatment of lung cancer - Tan BJ; Liu Y; Chang KL; Lim BKW; Chiu GNC (International Journal of Nanomedicine, 2012)
Bee-Jen Tan, Yuanjie Liu, Kai-Lun Chang, Bennie KW Lim, Gigi NC ChiuDepartment of Pharmacy, Faculty of Science, National University of Singapore, SingaporeBackground: Realizing the therapeutic benefits of quercetin is mostly hampered by its low water solubility and poor absorption. In light of the advantages of nanovehicles in the delivery of flavanoids, we aimed to deliver quercetin perorally with nanomicelles made from the diblock copolymer, polyethylene glycol (PEG)-derivatized phosphatidylethanolamine (PE).Methods: Quercetin-loaded nanomicelles were prepared by using the film casting method, and were evaluated in terms of drug incorporation efficiency, micelle size, interaction with Caco-2 cells, and anticancer activity in the A549 lung cancer cell line and murine xenograft model.Results: The incorporation efficiency into the nanomicelles was ≥88.9% when the content of quercetin was up to 4% w/w, with sizes of 15.4–18.5 nm and polydispersity indices of <0.250. Solubilization of quercetin by the nanomicelles increased its aqueous concentration by 110-fold. The quercetin nanomicelles were stable when tested in simulated gastric (pH 1.2) and intestinal (pH 7.4) fluids, and were non-toxic to the Caco-2 cells as reflected by reversible reduction in transepithelial electrical resistance and ≤25% lactose dehydrogenase release. The anticancer activity of quercetin could be significantly improved over the free drug through the nanomicellar formulation when tested using the A549 cancer cell line and murine xenograft model. The nanomicellar quercetin formulation was well tolerated by the tumor-bearing animals, with no significant weight loss observed at the end of the 10-week study period.Conclusion: A stable PEG-PE nanomicellar formulation of quercetin was developed with enhanced peroral anticancer activity and no apparent toxicity to the intestinal epithelium.Keywords: quercetin, polymeric micelles, PEG-PE, peroral drug delivery, lung cancer